An examination of middle leadership positions in Western Australian secondary schools - Brooks, Zoe A. (Curtin University, 2013)
This study examined the complexities inherent within secondary school middle leadership positions. These formal positions typically have line management accountability for the supervision of teaching and/or ancillary staff, through the Deputy Principal to the Principal. The study investigated the formal position requirements, as well as the professional perceptions and expectations of Western Australian, secondary school middle leaders. A mixed methods research design was used with a qualitative phase followed by a quantitative phase of data collection and analysis. The qualitative phase involved two stages of data collection and analyses. Firstly, a document analysis was conducted on the formal position descriptions of middle leadership positions in a purposive sample of ten Western Australian secondary schools. The formal position descriptions detailing the professional responsibilities of middle leaders were collected and analysed using content analysis techniques. Additionally, nine semi-structured interviews were conducted with a sample of subject, pastoral and program-based middle leaders across three Western Australian secondary schools. Semi-structured interviews were also conducted with a senior leader of each school sampled. The quantitative phase involved the construction and administration of an instrument designed to measure middle leaders’ perceptions of their role. The survey data were subsequently statistically analysed using the Rasch measurement model.The results of interviews with middle and senior leaders revealed six key aspects of the middle leadership position including: the dual and dynamic nature of middle leadership; the organisational functions of middle leaders; the problems and limitations associated with middle leadership positions; the effective qualities of middle leaders and their professional needs; the support and review requirements of the position, as well as the aspirations and role satisfaction of middle leaders. The results of the quantitative survey reveal middle leaders attitudes relating to five key facets of their position, including: role clarity; role authority; role support; role value and role fulfilment. The combined results of the qualitative and quantitative phases of the study resulted in the identification of seven key areas for the growth and development of middle leadership position in secondary schools. These include: the development of clear expectations and a school-wide understanding of the position; a focus on strengthening the influence of middle leaders on whole-school development; the provision of opportunities for leadership and management development; the need for peer support initiatives; the need for consistent performance appraisal and feedback processes; a focus on collaboration between middle and senior level school leaders; and the promotion of the position within the school and educational community.The implications of this study for schools include the need for clear role definition for middle leaders and targeted professional development opportunities, with a focus on leadership development. A significant outcome of this research is the construction of an instrument which measures middle leaders’ role perceptions. The instrument could be used by schools as a means of identifying the needs of middle leaders within a specific context and could also be usefully applied to future research into middle leadership. The work of middle leaders is vital in secondary schools and this research provides insight into the many dimensions of the role.